2019
DOI: 10.1093/jas/skz234
|View full text |Cite
|
Sign up to set email alerts
|

Effect of phytase on intestinal phytate breakdown, plasma inositol concentrations, and glucose transporter type 4 abundance in muscle membranes of weanling pigs1

Abstract: The objective of this present study was to determine the effects of phytase dosing on growth performance, mineral digestibility, phytate breakdown, and the level of glucose transporter type 4 (GLUT4) in muscle plasma membranes of weanling pigs. A total of 160 barrows were used in a randomized completely block design and assigned to 4 treatments for a 7-wk study. Depending on the feeding phase, diets differed in dietary calcium (Ca) and phosphorus (P) levels (positive control [PC]: 8 to 6.8g/kg Ca; 7.3 to 6.3 g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 51 publications
1
18
0
Order By: Relevance
“…Phytase supplementation for broiler diets has been associated with improvements in growth performance, nutrient digestibility, bone parameters, and its efficacy has been established with a large number of studies over time [ 8 , 22 , 34 , 35 ]. Recently, the study of the mucosa-associated microbiota in the jejunum has gained more attention due to the relevance for the metabolism of nutrients, stimulation of immune response, protection from pathogens, and stimulation of epithelium cell proliferation of the animals [ 25 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Phytase supplementation for broiler diets has been associated with improvements in growth performance, nutrient digestibility, bone parameters, and its efficacy has been established with a large number of studies over time [ 8 , 22 , 34 , 35 ]. Recently, the study of the mucosa-associated microbiota in the jejunum has gained more attention due to the relevance for the metabolism of nutrients, stimulation of immune response, protection from pathogens, and stimulation of epithelium cell proliferation of the animals [ 25 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, monogastric animals do not produce endogenous phytase and, consequently, the P content in the phytic acid form is not available for utilization by poultry [ 4 , 5 ]. Furthermore, phytic acid can also bind to proteins and enzymes like trypsin and α-amylase, inhibiting their activity and lowering protein and carbohydrate digestibility [ 6 , 7 , 8 ]. The undigested nutrients would be eliminated via excreta by the animals, raising an environmental concern [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…These performance responses were matched or exceeded with appropriate phytase supplementation. In addition, recent studies have reported a dose-dependent increase in phytate disappearance and myo-inositol concentrations in intestinal digesta of piglets with phytase [14,15,55,56]. Free myo-inositol is absorbed and can be detected in both portal and peripheral blood of pigs [15,52,56,57].…”
Section: Discussionmentioning
confidence: 99%
“…Typically phytases have been added to diets at a standard rate of 500 FTU/kg to target a moderate release of available P [12]. However, it has been demonstrated that using super-doses of phytase, at 3 to 5 times higher than the standard phytase dose, can lead to growth responses beyond what would be expected from the additional release of P [13][14][15]. A study in broilers suggested that 30 to 35% of the super-dosing response could be attributed to the generation of myo-inositol from the complete dephosphorylation of phytate [16].…”
Section: Introductionmentioning
confidence: 99%
“…The relative composition of the membrane phospholipids phosphatidylserine, phosphatidylinositol, phosphatidylcholine, and phosphatidylethanolamine affects membrane properties such as fluidity and receptor expression ( Fajardo et al., 2011 ). Indeed, our study in pigs ( Lu et al., 2019 ) showed that phytase supplementation increased the expression of GLUT4 in the longissimus dorsi muscle. Others have shown that phytase supplementation increased expression of sodium-dependent MI transporter, SMIT2, in the jejunum of chickens ( Walk et al., 2018 ).…”
Section: Introductionmentioning
confidence: 83%